Financial Accounting: Incentive Effects and Economic Consequences (Book Review). - Brief, Richard P. (The Accounting Review, 1989)
Abstract Reviews the book "Financial Accounting: Incentive Effects and Economic Consequences," by G. Whittred and I. Zimmer.